2019
DOI: 10.1186/s13012-019-0884-4
|View full text |Cite
|
Sign up to set email alerts
|

Physician-reported barriers to using evidence-based recommendations for low back pain in clinical practice: a systematic review and synthesis of qualitative studies using the Theoretical Domains Framework

Abstract: Background Adoption of low back pain guidelines is a well-documented problem. Information to guide the development of behaviour change interventions is needed. The review is the first to synthesise the evidence regarding physicians’ barriers to providing evidence-based care for LBP using the Theoretical Domains Framework (TDF). Using the TDF allowed us to map specific physician-reported barriers to individual guideline recommendations. Therefore, the results can provide direction to future interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 74 publications
(96 reference statements)
2
93
2
1
Order By: Relevance
“…Similar to a review by Hall et al, we found clinicians believed an absence of serious pathology on imaging provides reassurance to some patients. 95 We have shown that this was not always true from the patient's perspective; some patients with chronic low back pain seemed relieved by the presence of pathology on their imaging results-that is, the diagnostic grail. Indeed, a mega-ethnography by Toye et al found that patients with chronic musculoskeletal pain value having visual 'proof' in the form of imaging results to legitimise their invisible pain.…”
Section: Comparison With Existing Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…Similar to a review by Hall et al, we found clinicians believed an absence of serious pathology on imaging provides reassurance to some patients. 95 We have shown that this was not always true from the patient's perspective; some patients with chronic low back pain seemed relieved by the presence of pathology on their imaging results-that is, the diagnostic grail. Indeed, a mega-ethnography by Toye et al found that patients with chronic musculoskeletal pain value having visual 'proof' in the form of imaging results to legitimise their invisible pain.…”
Section: Comparison With Existing Literaturementioning
confidence: 98%
“…Patients, on the other hand, did not appear to be aware of such harms. Previous reviews have suggested a clinician's decision to ultimately pursue imaging is influenced by several complex factors including a belief that imaging is reassuring, 95 misconceptions about clinical guidelines, 12 and a desire to satisfy the patient. 96 Our review suggests that a mismatch in beliefs and understanding about the harms of imaging could be an important new target for intervention.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In our review, this covered a very wide range of issues: socio-economic issues such as having low income, societal issues like the in uence of media, health system issues like vaccine supply and cost, and individual access issues like distance and time. This was found to be a catch all category in many previous reviews of clinicians and patients using the TDF 12,[15][16][17][18][19] , so is not limited to the issue of vaccination barriers. For example, a review of barriers to low back pain guidelines found this domain was common to 4/5 clinician behaviours while many other domains were not covered at all 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[12] Although evidence for what is driving many of these behaviours is sparse, a recent systematic review of qualitative studies found that overuse of imaging may be in part due to patient beliefs and expectations. [13] For example, GPs reported that their patients believe an image will provide the best diagnosis for their back pain and it is easier to order an image than to try and explain otherwise. [13] Therefore, understanding the nature of patient beliefs and expectations regarding treatment will help coordinate efforts to improve consistency and quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…[13] For example, GPs reported that their patients believe an image will provide the best diagnosis for their back pain and it is easier to order an image than to try and explain otherwise. [13] Therefore, understanding the nature of patient beliefs and expectations regarding treatment will help coordinate efforts to improve consistency and quality of care.…”
Section: Introductionmentioning
confidence: 99%